2016
DOI: 10.1242/jcs.189795
|View full text |Cite
|
Sign up to set email alerts
|

Emerging biological roles of Cl− intracellular channel proteins

Abstract: Cl− intracellular channels (CLICs) are a family of six evolutionary conserved cytosolic proteins that exist in both soluble and membraneassociated forms; however, their functions have long been elusive. Soluble CLICs adopt a glutathione S-transferase (GST)-fold, can induce ion currents in artificial membranes and show oxidoreductase activity in vitro, but there is no convincing evidence of CLICs having such activities in vivo. Recent studies have revealed a role for CLIC proteins in Rho-regulated cortical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 103 publications
(164 reference statements)
0
76
0
Order By: Relevance
“…Contained in this overview is a summary of key findings made during the past decade on CLICs. For information on other chloride channels, the reader is directed to some recently published reviews (Argenzio & Moolenaar, ; Boedtkjer, Matchkov, Boedtkjer, & Aalkjaer, ; De Felice, ; Elborn, ; Jentsch, ; Miller, ; Ponnalagu et al., ; Sabirov, Merzlyak, Islam, Okada, & Okada, ; Stauber & Jentsch, ).…”
Section: Introductionmentioning
confidence: 99%
“…Contained in this overview is a summary of key findings made during the past decade on CLICs. For information on other chloride channels, the reader is directed to some recently published reviews (Argenzio & Moolenaar, ; Boedtkjer, Matchkov, Boedtkjer, & Aalkjaer, ; De Felice, ; Elborn, ; Jentsch, ; Miller, ; Ponnalagu et al., ; Sabirov, Merzlyak, Islam, Okada, & Okada, ; Stauber & Jentsch, ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Scheme 1B, the multistep synthesis of ferrocene-appended XB macrocycle 3.I was achieved by first react- Scheme ing bis(iodoalkyne) 4 and two equivalents of azide 5 via a copper(I)-catalysed azide-alkyne cycloaddition (CuAAC) protocol to form the bis-phenol precursor 6. Subsequent ring-closing was accomplished by Williamson ether synthesis [41] 4 ]PF 6 in CD 2 Cl 2 confirmed that the macrocycle was binding Cu I via the Lewis basic nitrogen atoms of the iodotriazole groups (see Figure S2-1, Supporting Information), a prerequisite for 3.I to be amenable towards CuAAC-AMT rotaxane synthesis. Indeed, a macrocycle containing the 1,3-bis(iodotriazole)benzene motif has been used to synthesise a family of XB rotaxanes by CuAAC-AMT, demonstrating that the benzene-iodotriazoles are conformationally-flexible enough to allow the Cu I to be coordinated in an endotopic fashion facing the interior of the macrocycle's cavity.…”
Section: Synthesis Of Halogen Bonding [2]rotaxanementioning
confidence: 99%
“…This suggested that although XB interactions were still primarily driving SCNbinding in the vicinity of the rotaxane cavity, the anion was too large to fit completely within it. For SO 4 2-( Figure S3-6, Supporting Information), very small shifts of all rotaxane proton resonances were seen, with the internal pyridinium proton H 1 only moving downfield by +0.03 ppm after addition of 10.0 equivalents of the oxoanion. Despite being capable of the strongest electrostatic attractions with the rotaxane, these results indicated that SO 4 2was interacting very weakly with rotaxane 1, which is probably a consequence of the anion's strong hydration in the aqueous solvent mixture and large size preventing access to the binding cavity.…”
Section: Anion Binding Studiesmentioning
confidence: 99%
See 2 more Smart Citations